NEEDS ANALYSIS OPEN ENDED LEARNING MODEL IN SMK - Purnamawati; KOMEINI, MUHAMMAD; Yahya, Muhammad (Pascasarjana Universitas Negeri Makassar, 2023)
This study aims to determine (1) analysis of the needs of open ended learning models for students; (2) analysis of the needs of open ended learning models for educators; (3) analysis of the needs of open ended learning models for learning management; (4) analysis of the needs of open ended learning models for lesson plans; (5) analysis of the needs of the open ended learning model for the implementation of learning; (6) the need for an open ended learning model for learning evaluation; The research subjects involved class XI for 3 schools (consisting of 265 students) selected by purposive sampling technique. Data was collected through observation, tests, interviews, and documentation and then analyzed using descriptive statistical analysis of percentages and frequency distribution tables. The results of the data analysis show that: (1) the need for an open ended learning model for students is 65%; (2) the need for an open ended learning model for educators is 55%; (3) the need for an open ended learning model for learning management is 75.83; (4) the need for an open ended learning model for learning planning is 82.22%; (5) the need for an open ended learning model for the implementation of learning is 69.44%; (6) the need for an open ended learning model for learning evaluation is 77.88%.